(x-3)^2-2(x+3)^2=(15-x-4)(x+6)
Răspunsuri la întrebare
Răspuns de
1
x²-6x+9-2(x²+6x+9)=(11-x)(x+6)
x²-6x+9-2x²-12x-18=11x+66-x²-6x
x²-6x-2x²-12x-11x+x²+6x=66+18-9
-23x=75
x=-75/23
x²-6x+9-2x²-12x-18=11x+66-x²-6x
x²-6x-2x²-12x-11x+x²+6x=66+18-9
-23x=75
x=-75/23
gaby106:
corect
Alte întrebări interesante
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Franceza,
9 ani în urmă
Matematică,
9 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă